2019
DOI: 10.1021/acsaem.9b00470
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Li/Li3BO3–Li2SO4 Interface and Application to Bulk-Type All-Solid-State Lithium Metal Batteries

Abstract: All-solid-state batteries (ASSBs) are potentially safe energy storage devices. The 90Li3BO3·10Li2SO4 (mol %) glass-ceramic is one of the promising oxide electrolytes due to its high ductility and ionic conductivity. Utilization of Li metal negative electrode enhances the energy density of ASSBs. Herein, the high electrochemical stability of the 90Li3BO3·10Li2SO4 electrolyte against Li metal negative electrode was demonstrated. The symmetric cells using a dense electrolyte body with relative density of 99% synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Also, it shows reduction peaks at less than 1.5 V at the first cycle for all SEs and that peaks were decreased after the second cycle. It suggests that a stable passivation layer was generated at the SE-Cu interface and suppressed further progress of the reduction reaction of Li 2 SO 4 , corresponding to a previous report . Regarding the reaction on the oxidation side of 2 V or higher, a redox peak of I was confirmed around 2.8 V in 0.42Li 2 SO 4 –0.28Li 2 CO 3 –0.30LiI, but any other redox peaks were not found until 3.2 V in the other SEs.…”
Section: Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Also, it shows reduction peaks at less than 1.5 V at the first cycle for all SEs and that peaks were decreased after the second cycle. It suggests that a stable passivation layer was generated at the SE-Cu interface and suppressed further progress of the reduction reaction of Li 2 SO 4 , corresponding to a previous report . Regarding the reaction on the oxidation side of 2 V or higher, a redox peak of I was confirmed around 2.8 V in 0.42Li 2 SO 4 –0.28Li 2 CO 3 –0.30LiI, but any other redox peaks were not found until 3.2 V in the other SEs.…”
Section: Results and Discussionsupporting
confidence: 81%
“…It suggests that a stable passivation layer was generated at the SE-Cu interface and suppressed further progress of the reduction reaction of Li 2 SO 4 , corresponding to a previous report. 28 Regarding the reaction on the oxidation side of 2 V or higher, a redox peak of I was confirmed around 2.8 V in 0.42Li 2 SO 4 − 0.28Li 2 CO 3 −0.30LiI, but any other redox peaks were not found until 3.2 V in the other SEs. Therefore, it is considered that SEs other than 0.42Li 2 SO 4 −0.28Li 2 CO 3 −0.30LiI are suitable for use as the SEs of a positive electrode or as a separate SE layer and 0.42Li 2 SO 4 −0.28Li 2 CO 3 −0.30LiI is suitable for a negative electrode.…”
Section: Resultsmentioning
confidence: 89%
“…A promising ternary glass oxide electrolyte of Li 3 BO 3 –Li 2 SO 4 –Li 2 CO 3 has been recently developed by Sakuda, Hayashi, and Tatsumisago. Although this glass electrolyte has a lower Li-ion conductivity compared with crystalline oxide electrolytes, it has a great advantage of mechanically soft property. In addition, this solid electrolyte could form a highly stable interface between the Li metal layer and the electrolyte layer, indicating good electrochemical stability for anode evaluation. Consequently, we expect that the solid electrolyte can be used to construct an oxide-based solid-state battery using our TiO 2 -based anodes at room temperature without a sintering process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, materials such as Li 3 OCl are difficult to synthesize and handle due to their extreme moisture sensitivity. Among those glass material candidates, Li 3 BO 3 (LBO) stands out because of its relatively low melting temperature (665 °C), moderate ionic conductivity (∼10 –6 S/cm), good stability in contact with Li metal and LLZT, and facile synthesis process. It was reported that the Li 2 CO 3 layer could be found at the LLZT surface and grain boundaries by its moisture contamination. , Applying the LBO layer and heat-treating the LBO-coated LLZT above 650 °C afterward may absorb some of the Li 2 CO 3 at the LLZT pellet surface to form Li 2.3 C 0.7 B 0.3 O 3 (LCBO), which delivers a moderate ionic conductivity (10 –6 to 10 –7 S/cm). , Table overviews the key properties of various glass interlayers which have been previously reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, materials such as Li 3 OCl are difficult to synthesize and handle due to their extreme moisture sensitivity. Among those glass material candidates, Li 3 BO 3 (LBO) stands out because of its relatively low melting temperature (665 °C), 29 moderate ionic conductivity (∼10 −6 S/cm), 30 good stability in contact with Li metal and LLZT, 31 and facile synthesis process. It was reported that the Li 2 CO 3 layer could be found at the LLZT surface and grain boundaries by its moisture contamination.…”
Section: ■ Introductionmentioning
confidence: 99%